Gas Expansion Three Days after Pars Plana Vitrectomy with Sulfur Hexafluoride 20% Tamponade following Carbon Monoxide Toxicity and Oxygen Therapy - Mojtaba Abrishami; Mehrdad Motamed Shariati; Ali Bolouki; Ghodsieh Zamani (Case Reports in Ophthalmological Medicine)
Purpose. To report an unusual case of gas expansion following oxygen therapy in a patient with sulfur hexafluoride (SF6) 20% tamponade after pars plana vitrectomy. Case Report. A 40-year-old man came to the clinic with severe ocular pain and redness and also vision decrease in his left eye three days after uncomplicated 23-gauge pars plana vitrectomy, internal limiting membrane peeling combined with phacoemulsification, and using 20% SF6 injection as a tamponade agent due to significant cataract and a full-thickness macular hole. In ophthalmic examinations of his left eye, high intraocular pressure (approximately 70 mmHg), a flat anterior chamber, and a gas-filled vitreous cavity were found. The patient had been hospitalized the day before due to carbon monoxide poisoning and had undergone oxygen therapy with a pure 100% mask for three hours. Conclusion. It seems that oxygen therapy or carbon monoxide poisoning increases the volume of gas in the patient’s vitreous cavity and the nonexpansile percentage of SF6 expands.